Income, Wealth and Health Inequalities - A Scottish Social Justice Perspective - Elspeth Molony; Christine Duncan (AIMS Press, 2016)
This paper considers health inequalities through a social justice perspective. The authors draw on a variety of existing sources of evidence, including experiential, scientific and contextual knowledge. The authors work with NHS Health Scotland, a national Health Board working to reduce health inequalities and improve health. Working closely with the Scottish Government and with a variety of stakeholders across different sectors, NHS Health Scotland's vision for a fairer, healthier Scotland is founded on the principles of social justice. The paper takes social justice as the starting point and explores what it means for two interlinked paradigms of social injustice-health inequality and income inequality. Utilising the wealth of evidence synthesised by NHS Health Scotland as well as drawing on the writings and evidence of philosophers, epidemiologists, the Scottish Government and international bodies, the authors explore the links between income and wealth inequality, social justice, the right to health and health inequalities. The paper ends by considering the extent to which there is appetite for social change in Scotland by considering the attitudes of the people of Scotland and of Britain to poverty, inequality and welfare.